â€œANALISIS UJI LAIK FUNGSI JALAN BERBASIS SISTEM INFORMASI GEOGRAFISâ€ (Studi Kasus : Ruas Jalan 40 kota Sofifi) - Zainudin, Zainudin; Gaus, Abdul; Rauf, Ichsan (CLAPEYRON: Jurnal Ilmiah Teknik Sipil, 2023)
Kilometer 40 of Sofifi City needs to be analyzed regarding the feasibility of road functions by monitoring and evaluating its technical standards because it is located in a special area for the government center so that access to land transportation increases and can reduce the level of feasibility of road functions. Analyze the feasibility of road functions on each segment of the Kilometer 40 road in Sofifi City and map the feasibility of road functions on the Kilometers 40 road in Sofifi City by using Arc Gis. The result technically for the section of km 40 Sofifi City, from a total of nine (9) segments, it can be determined that the road section has a "Technically Feasible" status, with an average functional feasibility test for segment 1 which is 96.3% in the Technical Feasible category, segment 2 which is 97.4% in the Technical Feasible category, segment 3 which is 94.6% in the Conditionally Good Level 1 (medium) category, km 40 Sofifi City, from a total of nine (9) segments, it can be determined that the road section has a "Technically Feasible" status, with an average functional feasibility test for segment 1 which is 96.3% in the Technical Feasible category, segment 2 which is 97.4% in the Technical Feasible category, segment 3 which is 94.6% in the Conditionally Good category Level 1 (medium), segment 4 which is 98.1% in the Technical Feasible category, segment 5 which is 96.8% in the Technical Feasible category, segment 6 which is 98.2% in the Technical Feasible category, segment 7 which is 97.2% in the Technical Feasible category, segment 8 which is 95.6% in the Technical Feasible category, segment 9 which is 97.5% in the Technical Feasible category.